Age affects the laying performance and egg hatchability of red-legged partridges (Alectoris rufa) in captivity - Barbosa, Agata (2010)
Red-legged partridge breeders are frequently reared in captivity with the aim of producing fertile eggs and chicks. However, little is known regarding the role of breeder age on fertility and egg production performance. Therefore, we investigated the effects of breeder age on egg size and shape, flock reproductive performance, fertility, hatchability, and embryonic mortality. In experiment 1, the effects of breeders' age on fertility, hatchability of eggs, and embryo mortality were evaluated. We found that partridge breeder age significantly affected the onset of egg laying, egg production, number and proportion of settable eggs, hatchability, and fertility. Specifically, 1-yr-old females laid their first egg 1 wk later than 2, 3, or 4-yr-old birds. Furthermore, 2-yr-old females produced a significantly higher number of settable and fertile eggs than other females (53.0 vs. 46.4 to 48.5) and had a lower incidence of embryo mortality. In experiment 2, we examined the effects of breeder age, egg size, and egg shape on egg hatchability. We found that small eggs (<17.6 g) had a significantly lower hatchability than medium (17.6 to 18.9 g) or large eggs (>18.9 g). However, we did not observe any significant correlation between egg shape and hatchability. These results suggest that red-legged partridge breeders attain maximum reproductive capacity at 2 yr of age and produce fewer eggs with lower weight and hatchability thereafter.